From Callus to Plantlet: unveiling the optimal hormonal synergy and sucrose supplementation for Zamioculcas zamiifolia micropropagation - Ashouri, Nafis; Daylami, Shirin Dianati; Karimi, Soheil (Ornamental Horticulture, 2025)
Zamiifolia (Zamioculcas zamiifolia) is an important plant in ornamental markets, characterized by a slow growth rate and low propagation efficiency. To establish an efficient propagation protocol for this species, two experiments were conducted. The first experiment aimed to optimize the micropropagation of Zamiifolia through callus induction. The second experiment evaluated the effects of the callogenesis medium on the growth and performance of regenerated plants in greenhouse. Leaf explants were incubated on the half-strength Murashige and Skoog medium (½MS) containing different combinations of benzyladenine (0, 4.4, and 8.8 μM BA) and naphthalene acetic acid (0, 2.7, 5.4, and 10.8 μM) and sucrose (2.0% and 3.0%). The highest callus induction rate and weight were obtained using 0.0 μM BA+2.7 or 5.4 μM NAA+3.0% sucrose. The obtained calluses were incubated on ½MS medium supplemented with different combinations of BA (0.0, 2.2, and 8.8 μM) and NAA (0.0, 1.1, and 2.7 μM) for shoot regeneration , with the highest proliferation efficiency on medium containing 2.2 μM BA. Rooting of shoots evaluated in ½MS containing indole-3-butyric acid (0.0, 2.5 and 5.0, μM IBA) and NAA (0.0, 37.2, and 2.7 μM) and 2.5 μM IBA medium was suggested, respectively. In the second experiment, plantlets were regenerated from calli induced on the four most effective media, and their growth was evaluated under greenhouse conditions. The best growth and health of micropropagated plants were obtained from callogenesis medium containing 2.7 μM NAA+3.0% sucrose. Excessive cytokinin accumulation following BA treatment impaired root and overall growth of micropropagated plants.